(untitled) (Research, Society and Development, 2021)
Violence against women is any gender-based act that results in, or is likely to result in, physical, sexual, psychological or distress for women. It should be addressed as a health problem where. Interdisciplinary vision is needed for follow-up or solution. It is an ecological study of multiple groups, which aims to describe the sociodemographic profile of violence against women from notifications in the Notifiable Diseases Information System of the city of Rio de Janeiro from January 2008 to 2017. 29,629 cases of violence against women were reported, predominantly in the age group of 20 to 29 years (29.1%), belonging to black/colored ethnicity (35.90%) and complete high school (11.30%). There was a predominance of physical violence with 58.9% of cases in the victim’s residence (53.6%). Violence against women is a serious public health problem. Due to the magnitude of the health consequences, its confrontation is challenging, requiring interprofessional and intersectoral actions, planning, applicability and evaluation of public policies.